Odpowiedzi

Najlepsza Odpowiedź!
2009-10-09T17:20:58+02:00
Mam dane:potrzebuje obliczyć q i n
a1 =1,
an =81,
Sn=121+40√ 3
Sn=a1*(1-q do potęgi n)/(1-q)

121+40√ 3=1*(1-q do potęgi n)/(1-q) /(1-q)
(121+40√ 3)(1-q)=1-q do potęgi n
an=a1*q do potęgi n-1
81=1*q do potęgi n-1
81=q do potęgi n-1
81=q do potęgi n:q
q do potęgi n=81q
podstawiam za q do potęgi n
(121+40√ 3)(1-q)=1-q do potęgi n
(121+40√ 3)(1-q)=1-81q
121+40√ 3-121q- 40√ 3q =1-81q
121+40√ 3-1=121q+ 40√ 3q-81q
120+40√ 3=40q+ 40√ 3q /:40
3+√ 3=q+√ 3q
3+√ 3=q(1+√ 3)
q=3+√ 3/(1+√ 3)
q=(3+√ 3)(1-√ 3)/(1+√ 3)(1-√ 3)
q=(3+√ 3)(1-√ 3)/(1-3)
q=3+√ 3-3√ 3-3/-2
q=-2√ 3/-2
q=√ 3
wracamy do 81=q do potęgi n-1
81=√ 3 do potęgi n-1
(√ 3)⁸=√ 3 do potęgi n-1
8=n-1
9=n
q=√ 3, n=9